Cell growth and cholesterol metabolism in human glucose‐ 6‐phosphate dehydrogenase deficient lymphomononuclear cells - B., Batetta (Cell Prolif, 2002)
Abstract. Atherosclerosis is an inflammatory‐fibroproliferative response of the arterial wall involving a complex set of interconnected events where cell proliferation (lymphomonocytes, and endothelial and smooth‐muscle cells) and substantial perturbations of intracellular cholesterol metabolism are considered to be among the main features. Glucose‐6‐phosphate dehydrogenase (G6PD), the key enzyme of the hexose‐monophosphate shunt pathway, is an essential enzyme involved in both cell growth and cholesterol metabolism, raising the question as to whether G6PD deficiency may have metabolic and growth implications in a deficient population. In the present study, we investigated cell growth and cholesterol metabolism in peripheral blood lymphomononuclear cells (PBMC) from G6PD‐normal (n = 5) and ‐deficient (n = 5) subjects stimulated with lectins (phytohaemoagglutinin and Concanavalin A). G6PD activity, DNA ([(3)H]‐thymidine incorporation) cholesterol synthesis and esterification ([(14)C]‐acetate and [(14)C]‐oleate incorporation), and G6PD, HMGCoA reductase and low density lipoprotein (LDL) receptor mRNA levels (RT‐PCR) all increased following lectin stimulation in both normal and G6PD‐deficient cells. However, these parameters were significantly lower in G6PD‐deficient cells (P < 0.05). It is of interest that G6PD‐deficient PBMC, which showed lower expression of G6PD and higher expression of the LDL receptor gene than normal PBMC under basal conditions, exhibited an opposite pattern after stimulation: G6PD and HMGCoA reductase being expressed at significantly higher levels in deficient than in normal cells (P < 0.05). We conclude that the reduced capability of G6PD‐deficient cells to respond to mitogenic stimuli and to synthesize cholesterol esters may represent favourable conditions for reducing the risk of cardiovascular diseases.